Agrochemicals Residues in Human Milk, Scientific Evidence or Overestimated Risk? - Raimundo, Rodrigo D.; da Silva, Tamara M.; Ferreira, Amanda V.; Santos, Bárbara S.; Carvalho, Tatiana D.; Fonseca, Ricardo L.A.; da Silva, Odair R.; Castanha, Cyntia S.C.; Daboin, Blanca E.G.; Fonseca, Fernando L.A. (Current Nutrition & Food Science, 2021)
Background: Exposures to agrochemicals can be directly through the handling of chemicals as well as indirectly when consuming food containing residues of them. Such exposure may affect the health of the population if accumulated in the human body, including in human milk. Objective: This literature review aims to assess the potential impact of agrochemical residues in human milk as a barrier to breastfeeding. Methods: The search followed PRISMA guidelines (Preferred Reporting Items for Systematic Reviews and Meta Analyses), by selecting original articles published between 1995 and 2019, extracted from the free access databases PubMed, Scielo, Web of Sciences and Scopus using as keywords: agrochemicals, pesticides, breastfeeding, human milk, contamination and infant. Medical Subject Headings (MeSH) were used as descriptors. Results: We selected 11 studies. Taking as inclusion criteria those most aligned with the objective of our study. Conclusion: The studies presented in this review ratified the benefits of breastfeeding compensating for the potential risks of agrochemical residues in human milk.
Keywords: infant